(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses the concept of “Homeland” in the literary texts of English language. The article analyzes poems and literary texts related to the oeuvre of outstanding poets. The author analyzed the core of the concept “Homeland” and the synonymous series of its periphery.